2021
DOI: 10.11591/ijpeds.v12.i2.pp1150-1161
|View full text |Cite
|
Sign up to set email alerts
|

Design and control of grid-connected solar-wind integrated conversion system with DFIG supplying three-phase four-wire loads

Abstract: <p>This paper describes the architecture and control of an autonomous hybrid solar-wind system (AHSWS) powered distributed generation system supplying to a 3ϕ-4 wire system. It includes a nonlinear controlling technique for maximum power point tracking (MPPT) used in doubly fed induction generator dependent wind energy translation scheme and solar photovoltaic system (SPVS). In the hybrid model, the DC/DC converter output from the PV system is explicitly coupled with the DC-link of DFIG's back-to-back co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…In (4) the actual parameters (tr, Mp, ts, and ess) are used to find the best solution for the objective function by ∑(𝑒𝑟𝑟𝑜𝑟𝑠) 2 of actual and desired parameters (trd, Mpd, tsd, and essd). In (5), The factor β is above 0.7 to minimize Mp and ess. meanwhile β is below 0.7 to minimize tr and ts [4].…”
Section: Validation Of the Implemented Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…In (4) the actual parameters (tr, Mp, ts, and ess) are used to find the best solution for the objective function by ∑(𝑒𝑟𝑟𝑜𝑟𝑠) 2 of actual and desired parameters (trd, Mpd, tsd, and essd). In (5), The factor β is above 0.7 to minimize Mp and ess. meanwhile β is below 0.7 to minimize tr and ts [4].…”
Section: Validation Of the Implemented Modelsmentioning
confidence: 99%
“…Various control techniques, for example, Appling adaptive, and fuzzy logic. The famous proportional-integral (PI) controller ,which is widely used in WT due to it is simple [4] and other studies found in [5]- [7]. However, it is not easy to get the required performance if its parameters isn't tunned.…”
Section: Introductionmentioning
confidence: 99%
“…A power maximization algorithm is used to maximize the performance of the Solar PV array as integrated with DC-DC convertor to produce a required duty cycle [15], [16]. Several algorithms were proposed in the literature to track and extract the maximum power point (MPP) from PV array such as hill climbing algorithm and slide mode control [17].…”
Section: Introductionmentioning
confidence: 99%
“…Geology collected the most outrageous power using multi-input help converters for cream energy [25]. The plan and control of an autonomous hybrid solar-wind system (AHSWS) controlled scattered age framework giving to a 3ϕ-4 wire framework [26]. The diminishing of expertise effectuated by the unreplenishable energy determination in view of the plunge of oil subordinates has made a substitute necessity for maintainable force sources to expect an essential part in giving power at a greater extension.…”
Section: Introductionmentioning
confidence: 99%